2017
DOI: 10.1371/journal.pone.0173645
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen gas alleviates oxygen toxicity by reducing hydroxyl radical levels in PC12 cells

Abstract: Hyperbaric oxygen (HBO) therapy through breathing oxygen at the pressure of above 1 atmosphere absolute (ATA) is useful for varieties of clinical conditions, especially hypoxic-ischemic diseases. Because of generation of reactive oxygen species (ROS), breathing oxygen gas at high pressures can cause oxygen toxicity in the central nervous system, leading to multiple neurological dysfunction, which limits the use of HBO therapy. Studies have shown that Hydrogen gas (H2) can diminish oxidative stress and effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…First, as shown in Ohsawa et al's study, hydrogen gas could selectively scavenge the most cytotoxic ROS, •OH, as tested in an acute rat model of cerebral ischemia and reperfusion (26). Another study also confirmed that hydrogen gas might reduce the oxygen toxicity resulted from hyperbaric oxygen via effectively reducing •OH (46).…”
Section: Hydrogen Gas Selectively Scavenges Hydroxyl Radical and Peromentioning
confidence: 80%
“…First, as shown in Ohsawa et al's study, hydrogen gas could selectively scavenge the most cytotoxic ROS, •OH, as tested in an acute rat model of cerebral ischemia and reperfusion (26). Another study also confirmed that hydrogen gas might reduce the oxygen toxicity resulted from hyperbaric oxygen via effectively reducing •OH (46).…”
Section: Hydrogen Gas Selectively Scavenges Hydroxyl Radical and Peromentioning
confidence: 80%
“…Hydrogen attenuates the oxidative damage between hydroxyl radicals and biologically essential molecules. By reducing the levels of oxidized macromolecules, mitochondrial and cellular injuries are greatly reduced [114]. Hydrogen has been shown to reduce hyperbaric oxygen-induced toxicity to PC12 cells, while also maintaining the antioxidant levels of superoxide dismutase (SOD), catalase and glutathione peroxidase.…”
Section: New Approach For Prevention and Treatment Of Cardiovasculmentioning
confidence: 99%
“…Hydrogen has been shown to reduce hyperbaric oxygen-induced toxicity to PC12 cells, while also maintaining the antioxidant levels of superoxide dismutase (SOD), catalase and glutathione peroxidase. These all contribute to hydrogens ability to alleviate the detrimental effects of hyperbaric oxygen [114].…”
Section: New Approach For Prevention and Treatment Of Cardiovasculmentioning
confidence: 99%
“…It is reported that hydrogen inhibited cellular damages through prevention of lipid peroxidation and DNA oxidation by selective-scavenging of hydroxyl radicals but not disturbing superoxide anion radicals, hydrogen peroxide, or nitric oxide in cells. 20 The production of malondialdehyde, an indicator of lipid peroxidation, is markedly reduced by hydrogen-rich saline in rat skin flap. 21 Our results suggest that hydrogen permeates deeply into skin and scavenges reactive oxygen species, resulting in inhibition lipid peroxidation in sebum-filled hair follicles ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 97%